Psychological distress on nurses: the role of personal and professional characteristics - Simães, C. (2019)
This study explored the role of nurses' personal and professional characteristics on the expression of psychological distress, overcoming the limitations of studying humans' responses to work environments using the stress-strain approach. The sample consisted of 2203 registered nurses working in Portugal. The investigation protocol included a Sociodemographic and Professional Questionnaire and the Portuguese version of the General Health Questionnaire-12. A high percentage of nurses (79.3%) showed levels of psychological distress, deserving for clinical attention. Significant differences were found between nurses with and without clinical symptoms of psychological distress. Female nurses, those working in primary health care, and nurses with no hobby and no physical exercise behaviors, presented significant levels of distress, deserving for clinical attention. These nurses reported high levels of anxiety/depression and social dysfunction. More, the absence of a hobby and the lack of physical exercise behaviors constituted as risk factors for the experience of clinical symptoms of distress, anxiety/depression and social dysfunction. These findings represent an important issue in occupational stress research, suggesting that leisure activities may be a protective factor for nurses’ mental health, acting as a “Daily Uplifts” for the stress recovery balance. Thus, in order to ensure the patients’ safety and the quality of health care, health organizations must consider nurses’ personal and professional characteristics that influence their mental health and global functioning when developing occupational health programs.